Evaluation of Vascular Remodeling in Carotid Atherosclerosis Among Type 2 Diabetes Mellitus Patients Using High-Frequency Ultrasonography Combined with Serum Resistin - Wang, Li-Kun; Wu, Xue-Liang; Shi, Li; Yang, Rui-Min; Liu, Wei-Liang; Hu, Zhen-Shun; Zhang, Zhi-Hua; Wang, Yi-Cheng (Experimental and Clinical Endocrinology & Diabetes, 2019)
Diabetes remains a long standing public health issue among the Chinese population, with an incidence of up to 11.6%, of which type 2 diabetes mellitus (T2DM) accounts for 85%–95%. During this study, we aimed to elucidate the value of high-frequency ultrasonography (HFUS) combined with serum resistin on vascular remodeling (VR) in carotid atherosclerosis (CA) among patients suffering from T2DM. A total of 432 T2DM were recruited and assigned into the short T2DM duration group (<5 years), middle T2DM duration group (5~10 years) and long T2DM duration group (>10 years), while another 172 healthy cases were recruited as the control group. The intima-media thickness (IMT) as well as plaque score, detection rate and type were detected by the HFUS. The respective blood pressure readings were measured and pulse pressure was calculated accordingly. The serum resistin level, remodeling incidence and type, levels of total cholesterol (TC), fasting blood glucose (FBG), low-density lipoprotein cholesterol (LDL-C), high-density liproprotein cholesterol (HDL-C), and triglyceride (TG) were measured. The correlation between IMT, the plaque detection rate and blood pressure were analyzed. A receiver operating characteristic (ROC) curve was constructed in order to evaluate the impact of VR in CA on T2DM patients who were solely using HFUS and serum resistin respectively, as well as a combination of HFUS with serum resistin. As In comparison with the control group, the short, middle and long T2DM duration groups all displayed increased IMT, plaque score and detection rate, serum resistin level and VR incidence, especially for the long T2DM duration group. Levels of TC, TG, FBG and LDL-C were much higher while HDL-C was lower among patients with T2DM than those in the control group. A positive correlation was detected between the disease course and IMT. The detection rate of plaque with thickening IMT exhibited upregulated levels when compared to those with normal IMT. The HFUS, serum resistin and HFUS combined with serum resistin respective areas under the ROC curve were 0.873, 0.867 and 0.923, respectively, suggesting that the combination of HFUS and serum resistin was superior to that of individual HFUS or individual serum resistin in regard to the impact of VR in CA on T2DM patients. The results of this study revealed that the combination of HFUS and serum resistin was superior to individual HFUS or individual serum resistin in relation to its ability to evaluate the impact of VR in CA in patients with T2DM.
Keywords: T2DM; Carotid atherosclerosis; Vascular remodeling; High-frequency ultrasonography; Serum resistin